A randomised comparative study of 1064 nm Neodymium‐doped yttrium aluminium garnet (Nd:YAG) laser and topical antifungal treatment of onychomycosis. Issue 12 (12th July 2016) - Kim, Tae In; Shin, Min Kyung; Jeong, Ki‐Heon; Suh, Dong Hye; Lee, Sang Jun; Oh, In‐Hwan; Lee, Mu‐Hyoung
Summary: Conventional treatments for onychomycosis include oral and topical antifungal agents. Although Nd:YAG laser has been reported to be effective, controlled studies combined or compared with conventional treatments are needed. To evaluate the efficacy of 1064 nm Nd:YAG laser for onychomycosis and compare outcomes with those of topical antifungal treatment and combination therapy. Patients were randomly divided into three groups: Laser (L); laser with topical antifungal therapy (L + T); and topical antifungal treatment (T). Laser treatment consisted of three or four sessions at 4 week intervals. Outcomes were assessed clinically and mycologically. In 217 nails of 56 patients, 76% in the L group and 71.8% in the L + T group experienced clinical responses, and 15.2% and 22.5%, respectively, were cured at 24 weeks. The clinical and cure rates of both groups were significantly greater than those of the T group. Six patients of the L group developed new infections, as did one patient in the L + T group and two patients in the T group. 1064 nm Nd:YAG laser shows clinically good responses in onychomycosis. Addition of topical antifungal agent did not appear to improve efficacy, but may have protected against new infection.